Assessing phylogenetic accuracy of plant species with chloroplast and nuclear genome specific markers - (:unkn) unknown (Nova Science Publishers, Inc., 2020)
In recent years, there has been a significant increase in the application of molecular genetic methods to more accurately and effectively evaluate the conservation and use of plant genetic resources. Molecular techniques also play an important role in the study of phylogenetics and species evolution, and have been applied to increase our understanding of the distribution and extent of genetic diversity between and within species. Improved marker methods combine the advantageous features of several basic techniques in order to increase sensitivity and resolution to detect genetic disruption and clarity. Molecular techniques have been applied in the analysis of specific genes. Several features, foremost its conservative mode of evolution, make chloroplast DNA an extremely valuable molecule for phylogenetic studies. Also, the Internal Transcribed Spacers -ITS are well protected nuclear genome region in eukaryotes, represents a very useful phylogenetic tool to analyze polymorphism at an intraspecific level. In this section, trnL-trnF was used as the chloroplast gene region and ITS region was used as the nuclear gene region in the identification and phylogenetic relationships of Colchicum species and the results of sequence analysis of both gene regions were evaluated using bioinformatic methods (phylogenetic tree, Principle Component Analysis-PCA, STRUCTURE analysis). © 2020 Nova Science Publishers, Inc. All rights reserved.
Keywords: Colchicum L.; ITS; Phlogeny trnL-trnF